EVALUATION OF COST BENEFIT ANALYSIS AS A TOOL ON FINANCIAL PERFORMANCE OF SELECTED PUBLIC SUGAR FIRMS IN KENYA - Wanyonyi, Wasike Edward; Ronald, Dr. Martin Onsiro; Mindila, Dr. Robert; Mwiti, Dr. Evans (IJRDO - Journal of Applied Management Science, 2016)
There has been a lot of concern over rising operational costs across the globe and more so particularly in Kenya due to energy costs, staff costs and even borrowing costs amongst many others. Sugar firms have over the last few years faced financial challenges causing uncertainty and anxiety to key stakeholders within and outside the company. The problem for the research was the apparent high operational costs that continued being exhibited which resulted in losses and therefore poor performance. The purpose of this study is to evaluate cost benefit analysis tools on financial performance of selected public sugar firms in Kenya. The specific objective of the study was to determine the extent of application of Cost-Benefit Analysis as a tool on financial performance. On average, the cost of producing a ton of sugar was highest at USD 870 and lowest at USD 300 in Kenya and Brazil which showed an extreme and unfavorable variance against sugar firms in Kenya of USD 570 (Eleventh Parliament,Third Session, 2015). The problem for the research was the apparent high operational costs that were being exhibited uncontrollably and which resulted in losses and therefore poor financial performance of the selected public sugar companies in Kenya. Cost - Benefit Analysis provides a means of appraising the future benefits in light of the costs that must be incurred in the present and its purpose is to measure the expected benefits of the investment so as to guide in rational resource allocation (Woodhall, 2004). Amongst the many accounting – based financial performance measurements are Return on Assets (ROA), Gross Profit Margin, Return On Investment (ROI) and Earnings Per Share (San & Heng, 2011). In the report of Cokins(2006), it stated that there was an overwhelming desire among firms to know well their costs and factors that drive them. It however found out that there is no clear understanding of the costs and the tools or methods to distinguish them. The reviewed literature above does not show any work done on evaluation of Cost Benefit Analysis Tools on financial performance of corporate organizations. A mixed methodology was used because